PELATIHAN PENGGUNAAN MEDIA SOSIAL DAN INTERNET SEBAGAI MEDIA PROMOSI PRODUK DESA CIJEMIT - Heru Budianto; Aji Permana; Dede Irawan; Adam Nurfauzan Subiyanto; Mita Hanifah Salma (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Promotion is a support in product marketing and sales. Promotion aims to ensure products are distributed to consumers. Cijemit Village is a village in the Ciniru Kuningan sub-district, West Java, which has village potential both in terms of culinary and tourism produced both individually and in groups. But so far the product is still not widely known due to the limited media promotion and marketing area. So far, people in Cijemit village are familiar with e-commerce sites, social media and others, but their use is still not optimal and limited for entertainment consumption and online shopping with the COD system. The service activities carried out aim to provide knowledge, insight, and knowledge in the form of seminars and training in the use of social media for product promotion so that they can develop. The implementation of this activity includes providing understanding, insight, knowledge and skills in managing promotions using social media in this case Facebook, Instagram and blogs. Based on the results of the analysis and discussion, it was found that there was an increase in knowledge, insight and knowledge in the use of social media as a promotional medium and increasing awareness of the use of social media in improving people's welfare.